2022
DOI: 10.1002/hsr2.816
|View full text |Cite
|
Sign up to set email alerts
|

The effect of virtual reality therapy and counseling on students' public speaking anxiety

Abstract: Background and Aims: One of the barriers to effective communication between speaker and listeners is public speaking anxiety (PSA). Over recent years, PSA has become common among students as the most widespread social anxiety (SA). Virtual reality (VR) and counseling therapy help reduce PSA. Therefore, the present study aimed to investigate the effect of VR therapy and counseling on students' PSA and SA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
0
4
0
6
Order By: Relevance
“…For example, psychology researchers have examined the impact of AR as a therapeutic approach for diagnosed anxiety disorders, specifically various phobias. 30 While studies suggest that VR can reduce anxiety in various contexts, such as medical procedures, 31 exam preparation, 32 and public speaking, 33 there remains a significant gap in the literature regarding the influence of VR on students' library anxiety. As far as we know, there is no dedicated study on the effect of VR on students' library anxiety, contrasting with the limited research on AR in this context.…”
Section: Metaverse For Library Anxietymentioning
confidence: 99%
“…For example, psychology researchers have examined the impact of AR as a therapeutic approach for diagnosed anxiety disorders, specifically various phobias. 30 While studies suggest that VR can reduce anxiety in various contexts, such as medical procedures, 31 exam preparation, 32 and public speaking, 33 there remains a significant gap in the literature regarding the influence of VR on students' library anxiety. As far as we know, there is no dedicated study on the effect of VR on students' library anxiety, contrasting with the limited research on AR in this context.…”
Section: Metaverse For Library Anxietymentioning
confidence: 99%
“…Virtual reality has been gaining attention as a potential tool for delivering therapy and counseling services, particularly in light of the COVID‐19 pandemic, which has led to an increased need for remote mental health services. While previous studies have demonstrated the effectiveness of VR in treating psychological disorders (Freeman et al, 2017; Hoffman, 2004; Maples‐Keller et al, 2017; Paul et al, 2022) and providing counseling services (Lin et al, 2021; Sarpourian et al, 2022; Wray & Emery, 2022), these studies were typically conducted on self‐developed platforms rather than publicly available social VR applications.…”
Section: Social Vr Encourages Self‐disclosure and Supports Mental Hea...mentioning
confidence: 99%
“…Es preciso señalar que las herramientas virtuales también pueden ser utilizadas para el abordaje de la ansiedad y depresión en estudiantes y profesores universitarios. En tal aspecto, la realidad virtual en conjunto con la terapia del asesoramiento estudiantil y docente ha demostrado disminuir los niveles de ansiedad, siendo necesarios para su efectividad, la confianza y el sentido de pertenencia entre los actores educativos (Sarpourian et al, 2022). En este sentido, es importante considerar en el diseño y evaluación de intervenciones, tanto las limitaciones metodológicas y las técnicas que son imprescindibles para el éxito de la realidad virtual, como medio para asegurar una consecución cabal de estándares educativos, lo que, además, amerita el cumplimiento de principios éticos internacionales, como la justicia, el beneficio mutuo y el respeto de las personas en los procesos de enseñanza y aprendizaje (Lacomba-Trejo et al, 2022).…”
Section: Introductionunclassified